2013
DOI: 10.1002/ddr.21076
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of New Pyridazin‐Based Thioderivatives as Formyl Peptide Receptor (FPR) Agonists

Abstract: A new series of pyridazinone-based thioderivatives and pyridazine analogs was synthesized and tested for their ability to bind to the three human formyl peptide receptor (FPR) isoforms (FPR1, FPR2, and FPR3) and to activate intracellular calcium mobilization and chemotaxis in human neutrophils. Among the pyridazin-3(2H)-one derivatives tested, analogs 8b and 8c were mixed FPR1/FPR2 agonists, with median effective concentration values in the micromolar range, and were able to activate chemotaxis and Ca 2+ flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…The homology model derived from the rhodopsin template shows that the FPR1 ligand binding site comprises two channels, two cavities, and the bottom [ 145 ]. Several amino acids are found to be involved in the interaction of FPR1 with agonists, including Asn 192 , Thr 199 , Arg 205 , Tyr 257 , and Thr 265 [ 80 , 145 , 146 , 212 ]. Docking studies with FPR1 non-peptide antagonists (including the bile acids DCA and CDCA) suggested that Thr 177 , Tyr 257 , and Thr 265 are involved in the formation of three stable H-bond interactions with DCA and CDCA in the docked pose [ 224 , 225 ].…”
Section: Structural Basis For Ligand Detectionmentioning
confidence: 99%
“…The homology model derived from the rhodopsin template shows that the FPR1 ligand binding site comprises two channels, two cavities, and the bottom [ 145 ]. Several amino acids are found to be involved in the interaction of FPR1 with agonists, including Asn 192 , Thr 199 , Arg 205 , Tyr 257 , and Thr 265 [ 80 , 145 , 146 , 212 ]. Docking studies with FPR1 non-peptide antagonists (including the bile acids DCA and CDCA) suggested that Thr 177 , Tyr 257 , and Thr 265 are involved in the formation of three stable H-bond interactions with DCA and CDCA in the docked pose [ 224 , 225 ].…”
Section: Structural Basis For Ligand Detectionmentioning
confidence: 99%
“…Additionally, they have R substitutions of SCH3 and OCH3, as well as R1 substitutions of I and SCH3, respectively. Both R and R1 substitutions are on substituted benzene rings [117]. (See Table 6 for the list of synthetic/small molecule non-peptide agonists).…”
Section: Synthetic Peptides and Non-peptide Small Moleculesmentioning
confidence: 99%
“…In previous studies, we identified several pyridazin-3( 2H )-one-based derivatives that showed an interesting profile as FPR agonists, combining an appreciable potency and differential selectivity toward the three human FPR isoforms [1721]. Key requirements for agonist activity of this class of compounds were the presence of a 4-bromophenylacetamide side chain at the N-2 position of the scaffold [17, 19] and the presence of a methyl group at C-6 [20].…”
Section: Introductionmentioning
confidence: 99%